1999
DOI: 10.1023/a:1020594223755
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Adhesion’an Integrated Molecular Process at the Leukocyte Plasma Membrane

Abstract: Leukocyte adhesion is of pivotal functional importance, because most leukocyte functions depend on cell-cell contact. It must be strictly controlled, both at the level of specificity and strength of interaction, and therefore several molecular systems are involved. The most important leukocyte adhesion molecules are the selectins, the leukocyte-specific beta2-integrins and the intercellular adhesion molecules. The selectins induce an initial weak contact between cells, whereas firm adhesion is achieved through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Despite the known confinement of CD11b and CD11c to a minority of T lymphocytes [9–11], we noted that in relation to CD4 + T cells, more CD8 + T cells had CD11b and CD11c on their surface and a higher expression of CD11b. The CD8 + cells that bear CD11b suppress T cell proliferation [12] and CD11c, which is expressed by some cytotoxic T cell clones, enhances cytolysis at the level of conjugate formation between effector and target cells [13].…”
Section: Discussionmentioning
confidence: 59%
“…Despite the known confinement of CD11b and CD11c to a minority of T lymphocytes [9–11], we noted that in relation to CD4 + T cells, more CD8 + T cells had CD11b and CD11c on their surface and a higher expression of CD11b. The CD8 + cells that bear CD11b suppress T cell proliferation [12] and CD11c, which is expressed by some cytotoxic T cell clones, enhances cytolysis at the level of conjugate formation between effector and target cells [13].…”
Section: Discussionmentioning
confidence: 59%
“…Because most leucocyte functions depend on cell–cell contact, they are strictly controlled both at the level of specificity and strength of interaction. Thereby, several molecular systems are involved beginning from the selectin‐induced weak contact between the cells, followed by the firm adhesion through integrin intercellular adhesion molecular binding, which allows the stimulating antigen presentation to occur [8]. In a previous study, it has been demonstrated that anti‐CD54 (anti‐ICAM‐1) antibodies effectively suppressed the proliferative responses of PBMC both in patients with atopic dermatitis and in healthy controls [23].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between cells are mediated by a magnitude of molecules. Different adhesion molecules, the most important of which are selectins, the leucocyte‐specific β 2 ‐integrins and the intercellular adhesion molecules (ICAMs), play a central role in the interaction of cells of the immune system [8]. The β 2 ‐integrins, lymphocyte function‐associated antigen‐1 (LFA‐1) and Mac‐1, consist of the same β subunit (CD18) and of a specific α subunit, α L (CD11a) in LFA‐1 and α M (CD11b) in Mac‐1.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphonuclear leukocyte (PMN) rolling and subsequent firm adhesion to the endothelium are a prerequisite for PMN transendothelial migration (51,16,6,18,38). A great deal of information has been generated on these initial adhesive interactions, and there is a general consensus on the molecular determinants of PMN rolling and adhesion (21,30,31,44,47).…”
Section: Introductionmentioning
confidence: 99%